β-Lactamase genes (blaCTX-M, blaSHV, blaTEM, blaOXA1 AND blaOXA2) and phylogenetic groups in ESBL producing commensal Escherichia coli isolated from faecal samples from dairy farm in the Municipality of Debar - Maksud Kerluku; Dean Jankuloski; Marija Ratkova Manovska; Mirko Prodanov; Biljana Stojanovska Dimzoska; Aleksandar Dodovski; Katerina Blagoevska (Macedonian Veterinary Review, 2023)
β-lactamases are a diverse class of enzymes produced by bacteria that present a major cause for resistance to β-lactams. In this study we analysed 159 fecal samples from dairy cows, for the presence of presumptive ESBL, AmpC, and carbapenemase-producing E. coli. Phylotyping was done using Clermont phylo-typing method, targeting arpA, ChuA, and YjaA genes, along with the DNA fragment TspE4.C2. Convetional PCR method was used to confirm the presence of bla genes among 39 phenotypically confirmed ESBL producing E. coli. The results showed presence of CTX-M, SHV, TEM and OXA1 bla genes in 28 (71.79%), 1 (2.56%), 29 (74.35%), 2 (5.12%) of isolates, respectively Twenty (51.28%) isolates showed presence of both blaCTX-M and TEM genes. The strain that carried the blaSHV gene was found to carry blaTEM gene as well, while one of the strains that carried blaOXA1 gene was also carrying blaCTX-M and TEM gene. The ration between isolates and phylo-groups was as follows: 9 (23.07%) strains were assigned to phyllo-group D; 14 (35.89%) to phyllo-group B; 16 (41.02%) to phyllo-group A. Out of the 39 strains where bla genes were identified, 29 (74.35%) were categorized as multi drug resistant.